ELDERLY DEPRESSION RATES - Hadiansyah, Tantan; Munawaroh, Fitri; Pragholapati, Andria (STIKes Maharani Malang, 2020)
Introduction: The world's aging population is increasing rapidly. The elderly experience a complex set of physical (lack of sleep, illness, low energy, poor concentration, poor appetite), psychological (negative thoughts, low self-esteem, sadness, despair) and social change (social withdrawal, decreased activity, decreased productivity, lack of initiation and depression are disorders that are often experienced by the elderly.This research method uses a quantitative descriptive study with a survey approach.This study aims to determine the level of depression in the elderly at the Tresna Werdha Social Protection Center (BPSTW) Ciparay, West Java.Samples were taken by technique consecutive sampling so that the number of samples is 60. Data collection techniques using the GDS (Geriatric Depression Scale) questionnaire Results and Analysis: 60 elderly people in the normal social protection center tresna wredha numbered 11 people with a percentage of 18.3%, who experienced mild depression amounted to 19 people with a percentage of 31.7%, who experienced d moderate depression numbered 16 people with a percentage of 26.7%, and those with severe depression were 14 people with a percentage of 23.3%. Discussion: We conclude that GDS is experienced by the elderly and a more in-depth study can be done.